SENI MEMAHAMI KABAR LANGIT:: Kritik terhadap Implementasi Hermeneutika sebagai Metode Tafsir Al-Qur’an - Khaidir, Piet Hizbullah; Wibowo, Amiruddin Hadi; Setiawan, Ahmad Bayu; Ulfiyatin, Anis (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2024)
Discussions by researchers of the Qur'an recently have reached a formulation regarding the importance of presenting a methodology that is comprehensive and relevant to current developments, so that the Qur'an can be interpreted in a relevant way to answer the problems of the times. Among the methodological problems raised as criticism of existing exegetical methods is the lack of space for contextualizing the interpretation of the Qur'an in discussing current and developing issues. Previous methods of interpreting the Qur'an mostly explained the meaning of language and reproduced discussions that may have been put forward several hundred years earlier. Against this methodological situation, a method of interpreting the Qur'an is proposed which adds to the previous method which touches more on the meaning of language or issues of jurisprudence, creed, etc., with a new method which includes historical analysis, investigation of the universal value of verses, as well as the universal mission of treatises. and Islamic law. The method proposed is hermeneutics. Since its emergence, hermeneutics has become a controversy between pros and cons. What is often discussed is the ideological and methodological face. This paper attempts to describe the material objects in this research descriptively and analytically. By reviewing the literature, this research describes the problems of presenting hermeneutics as a method of interpreting the Qur’an, as well as criticizing it. The results of the study in this manuscript are that there are several methodological and ideological issues as a critical discussion of the implementation of hermeneutics as a method of interpreting the Qur’an. The aim of this research is to criticize hermeneutics as a method of understanding the Qur’an. With this critical effort, it is hoped that the weaknesses and strengths of this method will be discovered. It is hoped that this criticism of hermeneutics can be an objective answer to the controversy over the presentation of hermeneutics as a method of interpreting the Qur’an.